(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article investigates space and time correlation (chronotop) in the poems by Ivan Drach, examines the dramatization of the poet’s thinking, and outlines philosophi-cal and psychological background of his poetic writings. The article also analyzes the influence of literary canon and tradition (T. Shevchenko, I. Franko, Lessya Ukrainka, P. Tychyna, M. Rylskuy, M. Bazhan) on Ivan Drach’s literary style and outlook. The author’s conceptual frame and structure of subjective consciousness as revealed in his poems are considered in the article.